PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA TUMOKANG BARU KECAMATAN DUMOGA UTARA KABUPATEN BOLAANG MONGONDOW - Ayu Andriani, Ni Made; Rares, Joyce Jacinta; Tampi, Gustaaf Budi (Sam Ratulangi University, 2017)
Summary: In act no 16 of 2014 explained that the construction of the village aims to improve the welfareof the village community and quality of life of mankind as well as pverty reduction through the fulfillment of basic needs, development of facilities and infrastructure of village, the development potential of the local economy as well as the utilization of natural resources and the environment in a sustainable way.The study uses qualitative methods. The informant is a government research village ( village chif), the village secretary, chairman of the BPD, head of community affairs and the village. The total number of informant there were as many as 10 people. Data collection with interview techniques, documentation, literature studies. While data analysis using descriptive analysis techniques of maleong.Based of the result of the research can be drawn the conclusion of participation in development in the village celebrated by Tumokang New Sub Regency North Bolaang Mongondow Dumoga, not to the maximum because of the willingness and ability of communities that are low and also human resourch community that is still underdeveloped because of the level of education of the community who only completed up to elementary level.Shove off the research results then put forth suggestions: (a) the government of the village is espected opportunities to the public to cntruction of the village (b) to move the willingness of the community to participate in development programs need to be held by the government’s own efforts in the delivery of information development (c)foster community awareness to participate, to socialize as well as cooperation from the government in order to make them aware of the meaning of their participation.Keywords: participation, the development of the village.